Pancharatha Garbhagriha of the Ghateshwar Temple - Temples of India Project Team (Jio Institute, 2024)
The pancharatha garbhagriha (sanctum with five offset projection) of the Ghateshwar Temple stands on a vedibandha (basal moulding) comprising a khura, kumbha (pot), kalasha (a pitcher), antarapata (recesses between moulding) and kapotapalika (cyma eve cornice). The jangha (wall) above has a bhadra (central offset), pratibhadra (offset flanking bhadra) and karna (corner offset). The bhadra has a niche installed with the figure of Andhkasuravadha. The pratiratha and karna are plain pilasters. The varandika (moulded parapet) above the jangha displays a checkered band between two kapotapalikas. The shikhara (superstructure) of the garbhagriha (sanctum sanctorum) is of the latina (vertical mono-spire) type.